The Role of Emotional and Expressive Function of Vocabulary in Teaching and Upbringing of Schoolchildren - Tkachuk, Halyna; Chervins’ka, Viktoriya (Pedagogical Discourse, 2013)
The article deals with the role of emotionally colored words, particularly their importance for enrichment and expressiveness of speech, emotional cognition of reality, and their influence on the reader, listener, interlocutor, the content of theoretical material for the treatment at the lessons of Ukrainian language aiming to get acquainted the pupil with such specfic layer of vocabulary, its types, stylistic functions is offered. It is mentioned that ability to explain the meaning of emotionally colored words, to define their functions in the text, to choose and appropriately fill into the speech emotionally colored phraseological units and deminutive vocabulary shold be formed.